2019
DOI: 10.1152/japplphysiol.00569.2019
|View full text |Cite
|
Sign up to set email alerts
|

Dissociating the effects of oxygen pressure and content on the control of breathing and acute hypoxic response

Abstract: Arterial oxygen tension and oxyhemoglobin saturation ([Formula: see text]) decrease in parallel during hypoxia. Distinguishing between changes in oxygen tension and oxygen content as the relevant physiological stimulus for cardiorespiratory alterations remains challenging. To overcome this, we recruited nine individuals with hemoglobinopathy manifesting as high-affinity hemoglobin [HAH; partial pressure at 50% [Formula: see text] (P50) = 16 ± 0.4 mmHg] causing greater [Formula: see text] at a given oxygen part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 40 publications
(50 reference statements)
0
19
0
1
Order By: Relevance
“…8C and D) for a given workload, but this too was not different between groups. Recently, we found that resting chemosensitivity to acute hypoxia and hypercapnia was not different between controls and subjects with HAH (Dominelli et al 2019).…”
Section: Ventilationmentioning
confidence: 87%
“…8C and D) for a given workload, but this too was not different between groups. Recently, we found that resting chemosensitivity to acute hypoxia and hypercapnia was not different between controls and subjects with HAH (Dominelli et al 2019).…”
Section: Ventilationmentioning
confidence: 87%
“…The peripheral chemoreflex is triggered by peripheral chemoreceptors located in the carotid bodies and aortic arch (Giussani et al 1993;Jensen & Hanson, 1995;Kumar & Prabhakar, 2012). P a,O 2 is classically considered the hypoxic stimulus, although there is evidence that arterial oxygen content may also be important, particularly at the aortic chemoreceptors (Kumar & Prabhakar, 2012;Dominelli et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Pa,O2 is classically considered the hypoxic stimulus, although there is evidence that arterial oxygen content may also be important, particularly at the aortic chemoreceptors (Kumar & Prabhakar, 2012; Dominelli et al . 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Transfusion of blood with altered oxygen affinity may also serve to improve oxygen unloading in peripheral tissues. [288][289][290]…”
Section: Blood Transfusionmentioning
confidence: 99%
“…Furthermore, less tissue edema would likely result since more administered volume would be retained within the vasculature. Transfusion of blood with altered oxygen affinity may also serve to improve oxygen unloading in peripheral tissues 288‐290 …”
Section: Impaired Metabolism‐perfusion Matching: Implications For Oxymentioning
confidence: 99%